Occlusion of left atrial appendage affects metabolomic profile: focus on glycolysis, tricarboxylic acid and urea metabolism - Sattler, Katherine; Behnes, Michael; Barth, Christian; Wenke, Annika; Sartorius, Benjamin; El-Battrawy, Ibrahim; Kuschyk, Jürgen; Hoffmann, Ursula; Papavassiliu, Theano; Fastner, Christian; Baumann, Stefan; Lang, Siegfried; et al. (Metabolomics, 2017)
BackgroundLeft atrial appendage (LAA) closure (LAAC) by implantation of an occlusion device is an established cardiac intervention to reduce risk of stroke while avoiding intake of oral anticoagulation medication during atrial fibrillation. Cardiac interventions can alter local or systemic gene and protein expression. Effects of LAAC on systemic metabolism have not been studied yet.ObjectivesWe aimed to study the effects of interventional LAAC on systemic metabolism.MethodsProducts of glycolysis, tricarboxylic acid and urea metabolism were analyzed by ESI-LC-MS/MS and MS/MS using the AbsoluteIDQ™ p180 Kit in plasma of 44 patients undergoing successful interventional LAAC at baseline (T0) and after 6 months (T1).ResultsDuring follow up, plasma concentrations of several parameters of glycolysis and tricarboxylic acid cycle (TCA) and urea metabolism increased (alanine, hexose, proline, sarcosine), while others decreased (aspartate, glycine, SDMA, serine). Multivariate linear regression analysis showed that time after interventional LAAC was an independent predictor for metabolite changes, including the decrease of SDMA (beta −0.19, p < 0.01) and the increase of sarcosine (beta 0.16, p < 0.01).ConclusionsSuccessful interventional LAAC affects different pathways of the metabolome, which are probably related to cardiac remodeling. The underlying mechanisms as well as the long term effects have to be studied in the future.